Evaluation of the factors affecting arsenic distribution using geospatial analysis techniques in Dongting Plain, China - Malik Muhammad, Akhtar; Tang, Zhonghua; Xiao, Tianyun (Frontiers in Environmental Science, 2022)
Due to high toxicity arsenic is regarded as a major global environmental pollutant. The present study investigated the potential factors affecting arsenic concentration in groundwater, surface water, and soil of the Dongting basin. The arsenic contamination potential prediction map and categories were developed using various GIS techniques such as Ordinary Kriging and Quantile method. Then “Raster calculator” tool was applied to verify the impact of the factors on arsenic concentration. Eighty-four single-factor, bi-factor, and multi-factor models were established to investigate effective combinations among factors of each phase. Additionally, statistic tests were computed to evaluate arsenic concentration between classes and factors. The arsenic concentration varies in groundwater from 0.0001mg L-1 to 0.1582mgL-1, while in surface water between 0.0001-0.0287 mgL-1 and soil sediments range 1.8-45.69mg/Kg. Groundwater resources of JunShan and GongAn were detected high risk for human health. Single factors showed best matching frequency of arsenic with a population of 66.86% in water and land use 73.19% in soil. Statistical calculation with percentage frequency factors also depicted a positive trend. The correlation of the factors with arsenic in soil and waters showed slow oxidation/reduction in the groundwater system. Treated portable water could be the best option to reduce the health risk of the community.